REPRESENTATION OF FEMINISM IN NAUSICAA’S CHARACTER EXPLICIT TRAIT - Laurencia Karenina Baskarani; Banung Grahita (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The media has the power to attract its audience to believe in what they consume. The depiction of feminism in female characters in animated films is still mainly focused on the visual aspect, with personalities that tend to be sexual and passive. Female character design needs special attention to show variations in capabilities, providing a positive view to the audience. Therefore, this research aims to identify design elements of characters’ explicit traits that can be used as categories in analyzing the representation of feminism in female character design. The research uses a content analysis method to analyze the animated film Nausicaä of the Valley of the Wind from Studio Ghibli. The movie was released in 1984 during a change in perspective towards women’s empowerment in Japan. The film is analyzed using three categories of characters’ explicit traits, which are body shape, costume, and attributes. The movie is separated into segments that fit the power-with category in the depiction of feminism in film. The researcher identifies each segment based on the categories. This research concludes that the characters’ explicit traits represent the third wave of feminism. Those traits explained the process and outcome of the character’s experience and fight throughout the film. They also portray an active female character.